Photography as a didactic resource to contextualize concepts of Analytical Chemistry (Research, Society and Development, 2019)
Analytical Chemistry is considered one of the most difficult curricular components in undergraduate chemistry, mainly because it is centered on chemical equilibrium. Thus, this study addresses the insertion of Observatory Scientific Photography in the context of the concepts of Analytical Chemistry, as a facilitator of teaching and learning, along with 18 students of Higher Education at the Federal University of Fronteira Sul, to observe the chemical balance present in daily life. In general, academics were restricted to bringing more examples from textbooks. However, the analysis of the photographs presented by the students showed the importance of motivating the students to seek knowledge in a contextualized and intentional way.